Research trends and hotspots of exercise for Alzheimer’s disease: A bibliometric analysis - Chen, Binglin; Fu, Yujie; Song, Ge; Zhong, Weiquan; Guo, Jiabao (Frontiers in Aging Neuroscience, 2022)
Objective: Alzheimer’s disease (AD) is a socially significant neurodegenerative disorder among the elderly worldwide. An increasing number of studies have revealed that as a non-pharmacological intervention, exercise can prevent and treat AD. However, information regarding the research status of this field remains minimal. Therefore, this study aimed to analyze trends and topics in exercise and AD research by using a bibliometric method. Methods: We systematically searched the Web of Science Core Collection for published papers on exercise and AD. The retrieved data regarding institutions, journals, countries, authors, journal distribution, and keywords were analyzed using CiteSpace software. Meanwhile, the co-occurrence of keywords was constructed. Results: A total of 1,104 papers were ultimately included in accordance with our specified inclusion criteria. The data showed that the number of published papers on exercise and AD is increasing each year, with papers published in 64 countries/regions and 396 academic journals. The Journal of Alzheimer’s Disease published the most papers (73 publications). Journals are concentrated in the fields of neuroscience and geriatrics gerontology. The University of Kansas and the USA are the major institution and country, respectively. The cited keywords show that oxidative stress, amyloid beta, and physical exercise are the research hotspots in recent years. After analysis, the neuroprotective effect of exercise was identified as the development trend in this field. Conclusions: Based on a bibliometric analysis, the number of publications on exercise and AD has been increasing rapidly, especially in the past 10 years. “Amyloid beta,” “oxidative stress,” and “exercise program” trigger the most interest among researchers in this field. The study of exercise program and mechanism of exercise in AD is still the focus of future research.